A smart drug delivery system responsive to pH/enzyme stimuli based on hydrophobic modified sodium alginate. (15th June 2020) - Gao, Xue; Yu, Zhe; Liu, Bingxin; Yang, Jixu; Yang, Xiaoyan; Yu, Yueqin
Graphical abstract: Highlights: HMA micelles could exist stably under physiological circumstance. HMA-DOX micelles could release most of the DOX in the presence of AFU under acidic condition. HMA micelles are more easily absorbed by cells and are non-toxic towards cells. Abstract: A biocompatible dual-stimuli responsive drug delivery for hydrophobic drugs based on self-assembled polymeric micelles was presented. Hydrophobic modified alginate (HMA), used dodecyl glycidyl ether as a hydrophobic group, could form self-assembled micelles in aqueous solution above the critical micelle concentration. Doxorubicin (DOX) was chosen as a model drug and successfully loaded in HMA micelles. The percentage of drug loading efficiency of the HMA was determined as 65.4% by using fluorescence measurement. The pH-triggered and enzyme-triggered release behavior of DOX from DOX-HMA micelles indicated that the release of DOX was accelerated in acidic medium and that the release rate was dramatically enhanced in the presence of Alpha-L-fucosidase. It was found that almost 80% DOX was released from the DOX-HMA micelles in the presence of AFU at pH 5.5. Moreover, in vitro drug release studies exhibited that the DOX-HMA was effectively taken up by the cancer cells, and the blank micelles showed low toxicity toward the cancer cells, while the drug loaded micelles had high toxicity, even than the free drugs. These results demonstrate that HMA may serve as a general platform for therapeutic delivery.